Translational immunologic safety evaluation: A perspective. (March 2013) - Descotes, Jacques
<x xml:space="preserve">Abstract</x> Although translational research is a rapidly evolving area of biomedical sciences, translational immunologic safety evaluation has so far attracted only very limited attention. Assays and animal models have been developed to identify immunotoxic hazards related to immunosuppression, but less attention has been paid to immunostimulation, hypersensitivity, and autoimmunity. Some of these assays and models are recommended by regulatory bodies, even though it is as yet unsure to what extent they can predict the potential of, or lack of, new chemical entities and drug candidates for inducing significant immunotoxic effects. A translational approach should attempt to standardize and validate those models, assays, and biomarkers that could be used in regulatory non-clinical safety studies as well as clinical studies. Beyond translational immunologic safety, immune monitoring during clinical studies is intended to identify and evaluate potential immune safety issues not seen in non-clinical studies. Based on this overview of the current knowledge, it can be concluded that much remains to be done to conduct translational studies helpful to enhance the immunologic safety of drugs and chemicals.